2023
DOI: 10.1063/5.0132254
|View full text |Cite
|
Sign up to set email alerts
|

Model of collective detachment in high-grade serous ovarian cancer demonstrates that tumor spheroids produce ECM to support metastatic processes

Abstract: High-grade serous ovarian cancer (HGSOC) metastasizes through transcoelomic spread, with both single cells and spheroids of tumor cells observed in patient ascites. These spheroids may form through single cells that detach and aggregate (Sph-SC) or through collective detachment (Sph-CD). We developed an in vitro model to generate and separate Sph-SC from Sph-CD to enable study of Sph-CD in disease progression. In vitro-generated Sph-CD and spheroids isolated from ascites were similar in size (mean diameter 51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…We observed changes in MMP-1 and/or MMP-10 in a subset of conditions, as well as decreases in Col I and fibronectin for all cell lines on stiffer substrates. This finding may seem in conflict with our prior study demonstrating a role for fibronectin in Sph-CD for reattachment; however, in that study, we demonstrated that the ECM was primarily produced by cells after they detached rather than taken from the substrate ( 9 ). Consistent with the proposed MMP-based mechanism, Piezo1 is linked to increased MMP-2 in endothelial cells ( 54 ) and human trabecular meshwork cells ( 55 ).…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…We observed changes in MMP-1 and/or MMP-10 in a subset of conditions, as well as decreases in Col I and fibronectin for all cell lines on stiffer substrates. This finding may seem in conflict with our prior study demonstrating a role for fibronectin in Sph-CD for reattachment; however, in that study, we demonstrated that the ECM was primarily produced by cells after they detached rather than taken from the substrate ( 9 ). Consistent with the proposed MMP-based mechanism, Piezo1 is linked to increased MMP-2 in endothelial cells ( 54 ) and human trabecular meshwork cells ( 55 ).…”
Section: Discussioncontrasting
confidence: 97%
“…Last, we considered the cell types to incorporate into our model. Our prior analysis of spheroids isolated from patient ascites suggested that they are composed primarily of epithelial cells ( 9 ). However, it is possible that the originating site has more cellular diversity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations